Using genre-based writing instruction to teach the writing of literary criticism - Ong, Wei Ann (Penerbit Universiti Kebangsaan Malaysia, 2016)
Literary criticism requires students to interpret and critique a literary text using literary theories. This study examined the use of genre-based writing instruction to teach the writing of literary criticism to a group of first year undergraduate students. The genre approach used was based on the Teaching Learning Cycle (TLC) developed by Systemic Functional Linguistics scholars. Past studies have shown that there is a dearth of research studying the use of the genre approach in teaching writing for literature in the ESL context. This study was undertaken as an exploratory case study, using pre-post tests and interview as data collection methods. An analysis of respondents’ essays revealed that they have improved in their ability to demonstrate all but a few of the rhetorical and linguistic conventions of a literary criticism. However, respondents who participated in the interview opined that they struggled in relating the exemplar studied during the deconstruction stage and felt that the writing instructor was too prescriptive in the joint-construction stage. Hence, the study revealed a need to hone students’ mastery of the subject content and language use. Writing instructors need to cater to the needs of the learners in carrying out the TLC.